THE EVALUATION OF HEALTH AND QUALITY OF LIFE OF PEOPLE WITH DISABILITIES LIVING IN SOCIAL SUPPORT CENTERS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article is dedicated to reviewing the issue of assessing the health and quality of life of people with disabilities living in social support centers. It discusses the key components that influence the health and well-being of this group, including physical condition, psycho-emotional health, social integration, and level of independence. Health assessment includes monitoring diseases, accessibility to medical care and rehabilitation, as well as support for psycho-emotional well-being. Quality of life, in turn, depends on living conditions, social activity, life satisfaction, and degree of involvement in public life. The article analyzes methods for assessing health and quality of life, including the use of questionnaires, medical examinations, and social research. It also examines key factors that affect the lives of people with disabilities in social support institutions and suggests ways to improve existing conditions to enhance their well-being. The conclusions aim to improve approaches to social services for people with disabilities, support their independence, and promote their social integration in society.